2022
DOI: 10.21608/ejhm.2022.263571
|View full text |Cite
|
Sign up to set email alerts
|

Sonohysterographic Evaluation of Cesarean Scar Defect after Purse-String versus Double-Layer Uterine Closure Techniques: A Randomized Controlled Trial

Abstract: Background: cesarean scar niche is one of the novels mentioned complications of cesarean section due to the rising numbers of cesarean sections and improved imaging modalities. The causes of cesarean scar niche are still being investigated, one of them is the uterine closure method that should be studied to pick up the best one to decrease the incidence of niche after cesarean delivery. Objective: The aim of this work was to find the best way of uterine closure decreasing the incidence of cesarean section nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Two studies found a significant decrease in niche prevalence and niche volume and a thicker residual myometrial thickness after double-layer closure [14,15]. Four randomized controlled trials compared doublelayer purse strings with single or double-layer closure in 218 women [16][17][18][19]. All studies showed a lower incidence of isthmocele and a thicker residual myometrial layer at the incision site favoring double-layer closure.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found a significant decrease in niche prevalence and niche volume and a thicker residual myometrial thickness after double-layer closure [14,15]. Four randomized controlled trials compared doublelayer purse strings with single or double-layer closure in 218 women [16][17][18][19]. All studies showed a lower incidence of isthmocele and a thicker residual myometrial layer at the incision site favoring double-layer closure.…”
Section: Discussionmentioning
confidence: 99%